A Complete Guide to Hyperthyroidism: What You Need to Know - Yahya, Najla Aulia; Nugraha , Kadek Nandita; Hardyningrat, Baiq Inna Dwi; Kirana, Devi Chandra; Kadarisma, Shofia; Nurhaliza , Siti; Ishlahi , Salsabila Dinda Nuril; Makbul, Ini Hidayat; Farras , Afif; Amanullah , Mohammad Sany Rosafi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Hyperthyroidism is a condition characterized by excessive thyroid gland activity, leading to an overproduction of thyroid hormones, namely thyroxine (T4) and triiodothyronine (T3). These hormones play a crucial role in regulating the body's metabolism, and their overproduction can affect various bodily functions. The aim of this article is to provide a comprehensive review of the epidemiology, etiology, clinical manifestations, and management options for hyperthyroidism. The review method involves a thorough analysis of relevant literature, including observational studies, clinical trials, and other related articles, to assess various aspects of the condition. This review identifies that hyperthyroidism is more prevalent in women, particularly with increasing age, with key risk factors including autoimmune diseases, genetic disorders, and environmental exposures. Clinical manifestations vary widely, from metabolic symptoms to systemic disorders, necessitating a proper diagnostic approach. Management strategies include the use of antithyroid medications, radioactive iodine therapy, and thyroid surgery. A deep understanding of hyperthyroidism is critical for effective diagnosis and treatment, as timely and appropriate interventions can improve patient outcomes and minimize long-term complications.